KAJIAN TINGKAT ADOPSI TEKNOLOGI PADA PENGELOLAAN TANAMAN TERPADU (PTT) PADI SAWAH (Oryza sativa L) DI KECAMATAN BOJA KABUPATEN KENDAL - Anggi Sahru Romdon; Suprapti Supardi; Lutfi Aris Sasongko (MEDIAGRO, 2012)
The improvements of rice production, which rice is the main food source for Indonesian people, have been carried out continuously; one of them is through the approach of Integrated Crop Management (ICM). ICM is not solely a technology or technology package but it is the approach of the production problem solution in a local region which applies appropriate technology and it is handpicked by farmers with the help of agricultural extension. The research was conducted to know how far the technology which has been introduced in the ICM are implemented or adopted by farmers viewed from the quality, speed and quantity. The introduced assembly technology is in form of new high-yielding varieties, high quality seed and labelled, increasing crop population through Jajar Legowo, balanced fertilizing, Crop Pests control through Integrated Pest Management approach, giving organic fertilizer, perfect cultivation, planting young seeds, planting 1-3 seeds per stick, intervallic watering, weeding with gasrok and proper harvesting after the harvest. The determination of sampling area is conducted purposively in Boja subdistrict, while the respondents sample are conducted in simple random sampling and obtained 70 farmers. Data analysis method which is used is the scoring based on the determiner component (impact point) while the level of adoption uses Likert's Summated Ratings (LRS) scaling method which are classified into three levels, namely the adoption of high, medium and low; with a low criterion (0,0 to 33,3 %), moderate (33,4 to 66,7%) and high (66,8 to 100%). The research results showed that the quality level of the technology adoption of integrated crop management of rice plant is categorized to moderate (60.61%), the adopted technology component is high-yielding varieties (72.38%), control of crop pests with integrated pest management approach (93.81%), proper soil management (97.14%), planting young seeds (70.71%), planting 1-3 seeds per stick (74.29%), intervallic irrigation (95.71%) and weeding with gasrok/hedgehog (88.98%) while other components are at medium and low categories. The speed and quantity of adoption are measured by the amount of farmers who adopted the ICM component, the analysis showed that the level of speed and quantity of the adoption is in the high category (76.48% and 75.73%). Based on these conditions, the elucidation of the technology which is summarized in the ICM still have to be carried out so that farmers can be more convinced to apply the ICM component. Keywords : adoption, ICM, rice plant